Classification of Franchising and Specifics of Its Types in Business Operation - BULAKH Т.; PLAKHOTNIKOVA, L.; HROMADSKYI, R. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2020)
The development of business can stuck in a series of problems related with market expansion, recruiting of staff in the dealer network, setting interaction channels etc. These can be dealt with by new economic mechanisms like franchising that allows for increasing the effectiveness of small business. But each of its type has advantages and shortcomings, which, if misunderstood, can cause serious risks to the operation of each partner and business on the whole. The article’s objective is to investigate criteria for classification of franchising and business specifics of its types. It is shown that franchising can take various types and forms in business operation, depending on the classification criteria. A detailed discussion of franchising types is given, classified by character of business operation, opportunities and intentions of franchisee, strategy for franchising business expansion, number of franchising enterprises owned by one franchisee, value of franchise, existence of intermediaries between franchiser and franchisee. It is argued that the above given classification allows one to position franchising types in business operation, choose the most appropriate type of franchising or a type of interactions with partners in creating a franchising enterprise, make projections for franchising-based businesses. It is emphasized that franchising is not an all-purpose tool for addressing all the problems of small business; it has a great many shortcomings that may be caused by possible dishonesty of a franchiser or rooted in the very nature of franchising. Two groups of shortcomings specific to franchising are discussed in detail. Advantages of the franchising system are demonstrated by comparing statistical data about the firms operated on franchising terms and by traditional methods; by highlighting the significant role of a ready-made standardized business plan provided by a franchiser to a franchisee, which helps insure the latter from business risks; and easy access of an entrepreneur deciding to launch own business (i. e. a franchisee) to bank loans.